An emotional support model in aging families: linking interaction patterns to positive mental health through social activity engagement and aging attitudes - Jianqian Wu; Yixuan Li; Qiuling Chao (Frontiers in Public Health)
ObjectivesFamily emotional interactions can be both supportive and detrimental, and their impact on positive mental health remains unclear. The study aimed to investigate the association and underlying mechanisms between family emotional interaction and positive mental health.MethodsA cross-sectional study was conducted among 1,200 older adults from Shanxi, Shaanxi, and Henan provinces in China. Data were collected via a questionnaire package assessing older adults' positive mental health, family emotional interaction, social activity engagement, and attitudes toward aging. Statistical analyses were performed using descriptive statistics, Pearson correlation, and path analysis.ResultsSocial activity engagement, psychological growth, physiological change, and emotional support were positively associated with positive mental health, and negative interaction was negatively associated with positive mental health. Emotional support was the main effect of promoting positive mental health among older adults. Social activity engagement and positive attitudes toward aging mediated the association between emotional support and positive mental health.ConclusionThis study presented an emotional support model among older adults. Being emotionally supported by families and actively engaging in social activities positively affects older adults' self-perceptions and promotes positive mental health, which are essential strategies for older adults to cope with potential stressors in later life. These findings advocate integrating family-centered interventions within gerontological practice to optimize emotional support across aging trajectories.